High Speed Rotor-Shaft Systems and Whirling Identification - Whalley, R (2007)
The transverse vibrations of shaft-rotor systems are considered. Interconnected assemblies of distributed parameter, compliant shafts, pointwise lumped rotor, and isentropic bearing units, are investigated. Analysis methods for shaft-rotor systems are formulated from the truncated, series expansion, of the rotor model, impedance matrix elements. Frequency domain evaluation of the determinant of the matrix model, enabling accurate validation, is incorporated. An illustrative application for a high speed, turbo-charger rotor system model is presented. Critical whirling speed conditions are identified. Alternative, established whirling speed evaluation techniques are investigated. Analysis, modelling accuracy, and the computational integrity of the procedures employed are emphasized.